Hubungan Citra Tubuh dan Faktor Lainnya dengan Status Gizi Siswi di SMA Kartika VIII-1 Kelas I dan II Jakarta Selatan - Dewi, Gusti Kumala; Anggraini, Wulan (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2024)
Adolescents according to the classification of the World Health Organization (WHO) are aged 10-19 years, but many adolescents do not go through this period optimally, even though during this early adolescence, body growth occurs very rapidly. In connection with this, one of the various problems that prevented him from passing this period properly was nutrition. Adolescents are faced with multiple nutritional problems, both excess and malnutrition (Freitag & Otaviani, 2010). A positive body image is one of the supporting factors for optimal nutrition in young women, however, nutritional problems can also be caused by various factors, either directly or indirectly. (Ambarwati, 2012). This study aims to analyze the relationship between body image and other factors with the nutritional status of female students class of I and II, in Kartika VIII-1 Senior High School, South Jakarta. This study used a cross sectional design. The population in this study was 143, with a sample of 32 female students who met the inclusion criteria taken by random sampling technique. This study used a 24-hour recall interview method and filled out questionnaires on attitudes, knowledge, body image, and physical activity as well as measuring nutritional status. The results of statistical tests using the Chi Square test showed that there was a relationship between knowledge of balanced nutrition and nutritional status with a p-value of 0.008, there was a relationship between energy intake and nutritional status with a p-value of 0.018, while the body image factor has a p-value of 1,000, the balanced nutritional attitude factor has a p-value of 0.292, and the physical activity factor has a p-value of 0.634, the results of these three factors indicate that there is no relationship between body image, balanced nutritional attitude, and physical activity with nutritional status. Keywords: iron intake, vitamin c intake, breakfast habits, learning concentration